Rethinking the category of State in Latin America: Recuperation of Latin American theoretical thought - Lujano, Cynthia (2007)
The author outlines the tendencies of Latin American Studies in the 20th Century, and discusses five historic moments that refer to key authors and representatives of critical Latin American thought. The questions How has state been studied in Latin America? and What challenges do institutional crisis pose to traditional concepts? define the article. Finally, the author evaluates the tendencies that have characterized every moment and proposes a possible line of investigation that she considers adequate for the complex and unsynchronized reality of Latin America.